STRATEGI PENGELOLAAN HUTAN DESA BUMI LESTARI DI DESA PENEPIAN RAYA, KABUPATEN KAPUAS HULU - Lestariningsih, Siti Puji; Roslinda, Emi; Azahra, Siva Devi; Destiana, Destiana (Lambung Mangkurat University-Indonesia, 2024)
The Village Forest Management Institution (LPHD) Bumi Lestari of Penepian Raya Village has obtained a forest management license since 2014. Village forest is one of the social forestry schemes that aims to improve community welfare through the management of forest natural resources. However, the management must be based on sustainable forest sustainability because the forest is a vital support. This study aims to formulate a management strategy for Bumi Lestari Village Forest based on internal (strengths and weaknesses) and external (opportunities and threats) factors. The survey method was applied by collecting data through interviews with all administrators and members of LPHD Bumi Lestari. All internal and external factors were scored and weighted to find strategy priorities based on SWOT. Based on the value of all factors, the internal factor value was 0.52 and the external factor value was 0.92. Bumi Lestari Village Forest management strategy is in Quadrant I. Strategic opportunities on maximum utilization of strengths to use available opportunities. The existence of assistance and funding, can be utilized to increase institutional capacity in terms of administration, mastery of technology, and innovation of processed non-timber forest product derivatives. An effective marketing network is needed to overcome obstacles in the form of the large amount of transportation bias through waterways in the village. In the field of conservation, LPHD Bumi Lestari has been based on smart patrols but there is a need to increase the use of technology. Strengthening partnerships with the government, academics, private foundations, and fellow LPHDs can be a strength for LPHD Bumi Lestari for better village forest management.